Customer Complaining Behavior in Retailing: An Empirical Study among Young Retail Customers - Rathnayake, C.V.; Perera, H.S.C.; Buddhika, S.A. (Indian Journal of Marketing, 2008)
This study investigates the nature and extent of customer complaining behavior in retailing. The focus of the study is to examine the complaining behavior of young retail customers in Matara District, Sri Lanka. Survey method was used as the main research method and a structured questionnaire was used to gather data from 80 customers. Survey results revealed that customers make complaints mainly to obtain the restitution. Conversely, the customers are somewhat altruistic and they prefer to make complaints to facilitate the service improvements. However, men tend more towards complaining to vent their anger. Mainly, it was recognized that young customers tend more towards private actions and comparatively, men are more aggressive. There, they switch the retailer, boycott the product/brand and/or spread negative word-of-mouth. Finally, it is notable that customers are somewhat passive in taking public actions in the face of a dejected transaction. However, they prefer to complain to the retailer first. They dislike to complain to a third party or to take legal actions against the retailer. Further, it is notable that that young retail customers view complaining as wastage of their time and effort. The study further highlights that the young retail customers are not "self blamers".